Strategy for developing excellent tourist destination (A case study of Gurabunga Village, Tidore Island Municipality, North Maluku) - Johan Fahri; Rueda Abubakar; Fadhliah M. Alhadar (Journal of International Conference Proceedings, 2022)
Tourism has been one of Indonesia’s most significant income contributors over the last few years. This study aimed to identify and analyze the development strategy of Gurabunga Village, Tidore Islands City, the Province of North Maluku. This study explored the villagers’ perspectives on the strategy for developing their village as a tourist village (Desa wisata). This study was qualitative research and used a case study approach to unveil the expected strategy that should be taken the villagers. The results strengthened that Gurabunga has been expected to be an excellent tourist destination due to three distinct elements coming in one place—location (749 m above sea level), culture (an essential region in the Tidore Kingdom), and culinary (traditional and cultural ceremonies). The results answered two research questions—where the first question concerns how to formulate strategies for developers-Gurabunga village as a community-based tourism village, and the last research question related to efforts to establish the village as a world-class tourist destination. Two main themes were derived from the first questions, while five main themes for the last question. Future studies should be able to increase the generalizability in using those eight identified themes to examine their fitness at different tourist villages. Keywords: tourist village, tourism strategy, villager’s empowerment